Analisis Kepuasan Pengguna Aplikasi Mobile By. U Menggunakan Metode EUCS End User Computing Satisfaction Pada Pengguna Provider By.U di Kota Surabaya - Hanif Ryandhika Ginaris; Arista Pratama; Eristya Maya Safitri (STIKes Ibnu Sina Ajibarang, 2024)
The development of digital services cannot be separated from users' habits in using smartphones and the affordability of internet access. Smartphone users want services that can carry out various activities easily, including telecommunications. This opportunity was captured by telecommunications companies by creating provider applications for smartphones. In connection with this, PT. Telekomunikasi Indonesia Tbk (Telkomsel) launched a new provider product called by.U. The purpose of this research is to determine the factors that influence user satisfaction with the by.U application based on the End User Computing Satisfaction (EUCS) model from William J. Doll & Gholamreza Torkzadeh (1988) with six variables consisting of content, accuracy, format , ease of use, timeliness, and satisfaction. This research used simple random sampling with a total of 60 respondents who were residents of the city of Surabaya who used the by.U application. The research results show that the variables of content and timeliness have a direct effect on satisfaction. Meanwhile, the variables accuracy, format and ease of use have a positive but not significant effect on satisfaction. Timeliness is the factor that has the most influence on satisfaction seen from the results of hypothesis testing which produces the largest path coefficient value, which is 0.268.